Aplicação da ferramenta SERVQUAL em uma pesquisa de satisfação com clientes de uma loja de roupas - Santos, Leticia Calaon (2018)
Knowing what the customer expects when entering the establishment and if it is possible to surpass the expectations of the same one has become a great challenge for the employees of the companies. The performance of customer satisfaction research has been fundamental to identify the problems and try to correct them, so the objective of this work is to conduct a customer satisfaction survey in a clothing store through the application of the SERVQUAL quality tool, created by Parasuraaman, Zeithaml and Berry (1988). With the application of the questionnaire it will be possible to identify the Gaps present between the expectation and the perspective of the client, and analyze which of the five general dimensions: Tangibility, Reliability, Sensitivity, Security and Empathy are considered more influential by the client in relation to the service provided.